2014 the 1st International Conference on Information Technology, Computer, and Electrical Engineering 2014
DOI: 10.1109/icitacee.2014.7065776
|View full text |Cite
|
Sign up to set email alerts
|

The influence of meteorological parameters under tropical condition on electricity demand characteristic: Indonesia case study

Abstract: As meteorological conditions can be unique in different countries and may have influence on electricity demand, providing demand model to analyze characteristic of demand is useful as obtained information can be used to manage related power systems better. This paper proposes regression based demand model to identify typical characteristic of demand in Indonesia more detail. Three different demand areas (Racing Area, Poltek-Area, and Paropo Area) in Makassar, Indonesia including their total demand (Total-Area)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…Reduksi konsumsi ini dapat maksimal salah satunya jika ditunjang dengan pengetahuan terkait penggerak konsumsi listrik sebagai dasar dalam melakukan berbagai aksi penghematan bagi pelanggan terhubung. Untuk itu, studi penggerak beban listrik penting dilakukan untuk konsumsi yang berkelanjutan, dan telah menjadi salah satu topik yang mendapat banyak perhatian peneliti dari berbagai negara [3]- [9].…”
Section: Gambar 2 Konsumsi Listrik DI Indonesia Untukunclassified
“…Reduksi konsumsi ini dapat maksimal salah satunya jika ditunjang dengan pengetahuan terkait penggerak konsumsi listrik sebagai dasar dalam melakukan berbagai aksi penghematan bagi pelanggan terhubung. Untuk itu, studi penggerak beban listrik penting dilakukan untuk konsumsi yang berkelanjutan, dan telah menjadi salah satu topik yang mendapat banyak perhatian peneliti dari berbagai negara [3]- [9].…”
Section: Gambar 2 Konsumsi Listrik DI Indonesia Untukunclassified
“…Indeed, several works have already shown the correlation between the electricity demand and weather variables [1][2][3][4][5]. Valor et al ( ) attributed the seasonal variation of electricity demand to weather variables and the increasing trend to socioeconomic factors [1].…”
Section: Introductionmentioning
confidence: 99%
“…Ali et al ( ), in their study entitled the relationship between extreme temperature and electricity demand in Pakistan, showed that the electricity demand is more for the summer season, and this demand will be higher (6785.6 GWh) in July 2020 due to rise in air temperature [4]. Akil et al ( ) showed a correlation between the electricity demand and weather variables in Indonesia [5]. Due to the fact that the weather variables may differ from one location to another, it is worth investigating the impacts of these variables on the electricity demand in a specific climate zone.…”
Section: Introductionmentioning
confidence: 99%
“…As an extended version of [6], this present study has focus to investigate demand characteristics mainly during maximum demand period for Indonesia context. Meteorological parameters and holidays are considered to explain pattern of demand in the observed period.…”
Section: Introductionmentioning
confidence: 99%